Degeneracy: Demystifying and destigmatizing a core concept in systems biology. Issue 3 (17th April 2014) - Mason, Paul H.
<x xml:space="preserve">Abstract</x> Often relegated to the methods section of genetic research articles, the term "degeneracy" is regularly misunderstood and its theoretical significance widely understated. Degeneracy describes the ability of different structures to be conditionally interchangeable in their contribution to system functions. Frequently mislabeled redundancy, degeneracy refers to structural variation whereas redundancy refers to structural duplication. Sources of degeneracy include, but are not limited to, (1) duplicate structures that differentiate yet remain isofunctional, (2) unrelated isofunctional structures that are dispersed endogenously or exogenously, (3) variable arrangements of interacting structures that achieve the same output through multiple pathways, and (4) parcellation of a structure into subunits that can still variably perform the same initial function. The ability to perform the same function by drawing upon an array of dissimilar structures contributes advantageously to the integrity of a system. Drawing attention to the heterogeneous construction of living systems by highlighting the concept of degeneracy valuably enhances the ways scientists think about self‐organization, robustness, and complexity. Labels in science, however, can sometimes be misleading. In scientific nomenclature, the word "degeneracy" has calamitous proximity to the word "degeneration" used by pathologists and the shunned theory of degeneration once promoted by eugenicists. This article disentangles the concept of degeneracy from its close etymological siblings and offers a brief overview of the historical and contemporary understandings of degeneracy in science. Distinguishing the importance of degeneracy will hopefully allow systems theorists to more strategically operationally conceptualize the distributed intersecting networks that comprise complex living systems. © 2014 Wiley Periodicals, Inc. Complexity 20: 12–21, 2015